Effects of Profitability towards Enterprise Value with Corporate Social Responsibility Performance and Brand Value as Mediating Variables - Gregorios Ronald; Hatane Semuel (Petra International Journal of Business Studies, 2022)
Currently, many companies are taking many actions to put their most vigorous efforts into enterprise value creation, which enables the company to achieve its highest market capitalization. They plan and do many strategies, such as value-added creation by creating intangible values through CSR activities, creating CSR performance, and brand value creation through brand valuation. This research seeks to determine whether companies' profitability, ROA, and ROE affect the enterprise value. Therefore, two mediating variables, CSR performance and Brand Value, have been set to analyze whether one impacts another. To do research, the researcher utilizes secondary data, which is the data that has been collected by someone other than the researcher. The finding shows that companies' profitability has no impact on the enterprise value and CSR performance.; On the other hand, the results show a strong relationship between brand value and enterprise value, and brand value is a mediating variable between companies' profitability and enterprise value.